Optimization and characterization of cast in-situ alkali-activated pastes by response surface methodology - Mohammed, B.S. (Elsevier Ltd, 2019)
Due to its low carbon footprint and the capacity to be used for in situ applications, cast in-situ geopolymers are recognized as a feasible substitute of Portland cement. One of the limiting factors of using geopolymer in concrete sectors is dealing with viscous and dangerous alkaline alternatives, making it hard to adopt for mass concrete manufacturing. The advanced binder comprises of aluminosilicate components and granular sodium metasilicate to which water has been added like OPC. This document reports on the novel experimental method of producing cast in-situ alkali-activated binders using fly ash, ground granulated blast furnace slag (GGBS) and anhydrous sodium metasilicate. The defined method is described with a logical experimental study conducted to examine a feasible manufacturing method for casting in-situ geopolymer production. Replacement concentrations for slag were 0â100 percent by fly ash weight, while activator is used at 8â16 of the complete binder content. The strengths, absorption rate and microstructural behaviour of cast in-situ alkali-activated pastes were regarded for up to 28 days. The resistance development of one-part/cast in-situ alkali-activated binders was discovered to be comparable to that of OPC. Microstructural assessment disclosed that the incorporation of GGBS in the paste resulted in structural changes of the in-situ geopolymer paste that could be attributed to the creation of C-A-S-H gel owing to the existence of extremely reactive alumina and silica in the source materials. Using the variance analysis, the impact of slag and sodium metasilicate activator on the behaviour of cast in-situ geopolymer pastes was acquired. The defined models were discovered to be important for all P-value reactions of <5. Results of numerical optimizations showed that the best mixture can be obtained by replacing 100 percent fly ash with slag and 11.19 percent sodium metasilicate with total binders weight. Â© 2019 Elsevier Ltd